Sastra Satire Kitab Yunus: Analisis Naratif Prolog dan Epilog Kitab Yunus - Muryati Muryati; Gernaida Pakpahan; Junifrius Gultom (Sekolah Tinggi Teologi Paulus Medan, Sumatra Utara, 2020)
The anomaly of Jonah's attitude in rejecting God's call (Jonah 1) and his anger at Nineveh's conversion caused various opinions on the genre of his book. This encourages the need to produce new findings to narrow the view of experts by placing the book of Jonah as satire literature. The purpose of this research is to describe the satire elements contained in the prologue and epilogue of the book of Jonah. The method used in this research is a narrative approach using a modified method that departs from the four narrative elements namely the narrator, character (characterization), point of view, and storyline then combined with some elements of general interpretation in it. through the narrative analysis method, the researcher sees the text as a